2006
DOI: 10.1089/thy.2006.16.1113
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Sandostatin Treatment in Patients with Progressive Thyroid Cancer and Iodine-Negative But Somatostatin-Receptor–Positive Metastases?

Abstract: Our data demonstrate that all of our patients treated with a somatostatin analogue showed clinical progression and that our attempt to achieve a stabilization of the disease failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
14
1
2
Order By: Relevance
“…Sst subtypes 2 and 5 are involved in the control of hormone secretion as well as cell growth, while sst1, 3 and 4 are mostly implicated in non-hormonal functions [10][12]. Somatostatin analogue treatments used in clinical practice involve binding of sst2 and 5 with different affinity [13], [14], with sst2 having the maximal binding affinity to the most currently used compounds, octreotide and lanreotide [15], while pasireotide is a new compound targeting sst5 with higher affinity [16], [17]. Recently, two new functional human sst5 variants have been identified, the so-called sst5TMD4 and sst5TMD5, generated through non-canonical splicing, and displaying unique molecular/functional features [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sst subtypes 2 and 5 are involved in the control of hormone secretion as well as cell growth, while sst1, 3 and 4 are mostly implicated in non-hormonal functions [10][12]. Somatostatin analogue treatments used in clinical practice involve binding of sst2 and 5 with different affinity [13], [14], with sst2 having the maximal binding affinity to the most currently used compounds, octreotide and lanreotide [15], while pasireotide is a new compound targeting sst5 with higher affinity [16], [17]. Recently, two new functional human sst5 variants have been identified, the so-called sst5TMD4 and sst5TMD5, generated through non-canonical splicing, and displaying unique molecular/functional features [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Papotti et al (25) did not detect SSTR expression in normal thyroid tissue by IHC. Moreover, clinical trials have shown that SSTR2-specific agonists such as octreotide have no or only little antiproliferative effect on thyroid carcinomas (26,27). Therefore, the specificity and cellular origin of the SSRS findings in CNs, HNs, PCs, and GD are currently unclear and demonstrated partly only in case reports.…”
Section: Introductionmentioning
confidence: 99%
“…In normal human thyroid tissue, SSTR3 and 5 seem to be the predominant somatostatin receptor subtypes according to Ain et al (22). However, SSTR2 specific agonists like octreotide do not or have only little antiproliferative effect on thyroid carcinoma as shown in clinical trials (23,24). Druckenthaner et al (13) reported expression of SSTR2 mRNA but lack of SSTR2 immunohistologic staining in normal thyroid tissue.…”
Section: Introductionmentioning
confidence: 99%